The Dialogical Patrol Efforts of the Sabhara Unit in the Prevention of Criminal Acts of Theft with Aggravated Circumstances - Dibyo Joyo Manggolo (Police Studies Review, 2021)
Preventive efforts that have been made to reduce the crime rate will be very influential if done properly and consistently. The author wants to do research, especially regarding dialogical patrols carried out as a preventive effort by the Sabhara Unit so that it can reduce the number of criminal cases of theft by weighting the Padangsidimpuan Police so that the author will put it into scientific papers. In the Padangsidimpuan Police, as well as describing the factors that influence the prevention of theft by using the dialogical patrol method. In this study, a qualitative approach was used with the method of field research through interviews, observation, and document study. Based on the research results of the Sabhara Unit Dialogical Patrol Effort in Preventing Crime of Theft by Giving Up at the Padangsidimpuan Police, it was carried out well and the community was cooperative in carrying out the appeal of the patrol officer. The cycling patrol program and the implementation of the PSBB are supporting factors for the prevention of criminal acts of theft by weight, however, the limited number of personnel and the patrol's targets is an obstacle. Keywords: dialogical patrol, effort, weighted theft.